Experimental Study on the Distribution Characteristics of CO2 in Methane Hydrate-Bearing Sediment during CH4/CO2 Replacement - Jianye Sun; Xiluo Hao; Chengfeng Li; Nengyou Wu; Qiang Chen; Changling Liu; Yanlong Li; Qingguo Meng; Li Huang; Qingtao Bu (Energies, 2022)
CH4/CO2 replacement is of great significance for the exploitation of natural gas hydrate resources and CO2 storage. The feasibility of this method relies on our understanding of the CH4/CO2 replacement efficiency and mechanism. In this study, CH4/CO2 replacement experiments were carried out to study the distribution characteristics of CH4 and CO2 in hydrate-bearing sediments during and after replacement. Similar to previously reported data, our experiments also implied that the CH4/CO2 replacement process could be divided into two stages: fast reaction and slow reaction, representing CH4/CO2 replacement in the hydrate-gas interface and bidirectional CH4/CO2 diffusion caused replacement, respectively. After replacement, the CO2 content gradually decreased, and the methane content gradually increased with the increase of sediment depth. Higher replacement percentage can be achieved with higher replacement temperature and lower initial saturation of methane hydrate. Based on the calculation of CO2 consumption amounts, it was found that the replacement mainly took place in the fast reaction stage while the formation of CO2 hydrate by gaseous CO2 and water almost runs through the whole experimental process. Thus, the pore scale CH4/CO2 replacement process in sediments can be summarized in the following steps: CO2 injection, CO2 diffusing into sedimentary layer, occurrence of CH4/CO2 replacement and CO2 hydrate formation, wrapping of methane hydrate by mixed CH4-CO2 hydrate, continuous CO2 hydrate formation, and almost stagnant CH4/CO2 replacement.